Baptism as a Test Case for the Nature and Limits of National Theology - Saucy, Mark (Bogoslovskie razmyšlenija, 2007)
In its source and substance evangelical national theology is bound by the canon of Scripture and the transcultural message of good news recorded therein. This essay attempts to apply the limits of the Gospel, Scripture’s evangelium, to the question of the meaning and practice of baptism. Exegesis of relevant texts, biblical theology and church history are explored for conclusions. First, exegesis does not appear to give baptism a substantive role in the New Testament in creating eternal life, placing us into Christ, or giving the Holy Spirit. Faith stands preeminent and alone for all these blessings. Second, the apostolic theology of faith, grace, good works and the place of Christ’s cross in the Gospel recognizes baptism as the expression of obedience by an already saved person. It also indicates the spiritual blessings that obedience in baptism do bring. In Scripture baptism is presented as a means to strengthen and support spiritual life rather than a means necessary to gain that life. Baptism does not create anything; it sustains and enriches something. Finally, Church history indicates that the question of baptism’s necessity does not appear to divide along the cultural boundaries. It divides along the eternal boundary of Gospel and Not-Gospel. When shrouded in later sacramental theology, baptism mutes the Gospel’s requirement of faith alone. The essay concludes with a call to the biblical pattern where baptism is an initiatory rite administered in close chronological proximity to believing faith. Separating baptism from faith artificially de-stabilizes the faith-obedience core of the Gospel’s demand. It elicits questions as to the efficacy of baptism in itself—questions Scripture does not raise.